Analysis of the expression of PHTF1 and related genes in acute lymphoblastic leukemia. Issue 1 (December 2015) - Huang, Xin; Geng, Suxia; Weng, Jianyu; Lu, Zesheng; Zeng, Lingji; Li, Minming; Deng, Chengxin; Wu, Xiuli; Li, Yangqiu; Du, Xin
Abstract Background Previous study showed that downregulatedBCL11B expression in T cell acute lymphoblastic leukemia (T-ALL) cell line Molt-4 inhibited cell proliferation and induce apoptosis, which may be related toPHTF1 gene overexpression. The objective of this study was to investigate the expression ofPHTF1 and related genes in ALL and further explore its function in T-ALL cell lines. Methods Real-time PCR was used to determine the gene expression level ofPHTF1 in hematologic malignancies. ThePHTF1, BCL11B, FEM1B andApaf -1 gene expression levels and correlations were analyzed in patients with primary ALL (including T-ALL and B-ALL) and healthy individuals (HIs). Inhibition and overexpression ofPHTF1 by lentiviral transduction were performed using the Molt-4 and Jurkat cell lines. Cell growth and apoptosis were measured by the Cell Counting Kit-8 assay and flow cytometry, respectively. UponPHTF1 overexpression, theBCL11B, FEM1B andApaf -1 gene expression levels were determined by real-time PCR. Results PHTF1 overexpression was found in both T-ALL (p = 0.004) and B-ALL (p < 0.001) groups compared with HIs group. A trend toward a negative correlation between thePHTF1 andBCL11B genes was detected for the T-ALL group, while positively correlated expression was found for thePHTF1 andBCL11B genes in HIs (P = 0.001).FEM1b andApaf -1 overexpression was found in recently diagnosed ALL patients compared with HIs (p < 0.05). Positively correlated expression was found for thePHTF1, FEM1b andApaf -1 genes in patients with ALL (p < 0.05) and HIs (p < 0.05). Direct up-regulation ofPHTF1 expression inhibited the proliferation of Jurkat and Molt-4 cells and effectively induced apoptosis in Molt-4 cells. Direct inhibition ofPHTF1 expression had no significant effect on the proliferation or apoptosis of Jurkat and Molt-4 cells.FEM1b andApaf -1 overexpression, which did not obviously alter theBCL11B expression level, was detected inPHTF1 -transduced T-ALL cell lines. Conclusions PHTF1 overexpression is responsible for regulating cell proliferation and apoptosis in T-ALL cell lines.PHTF1 may be a tumor-suppressor like gene and a therapeutic target for triggering thePHTF1 -FEM1b -Apaf -1 apoptosis pathway.